Reactivity of Binary Construction and Demolition Waste Mix as Supplementary Cementitious Materials - Raquel Vigil de la Villa Mencía (MDPI AG, 2021)
Calcareous and siliceous CDW wastes from concrete and glass wastes when mixed in binary mixtures has been analyzed in this study. Fine CDW fractions (<5 mm) of different sorts are selected: siliceous waste (HsT), calcareous waste (HcG) and laminated glass waste. The binary mixtures HsT/glass and HcG/glass at mix-proportions of 1:1, 2:1 and 1:2, respectively, are analyzed with a range of characterization techniques (XRD, TG/DTA, SEM-EDX, NMR, FT-IR) in the pure pozzolan/lime system over a reaction time of 90 days. The results showed that the incorporation of highly reactive recycled glass modified the pozzolanic reaction of the binary mixtures with respect to each particular concrete waste (of low activity). The principal mineralogical phases of the reaction were calcite and C–S–H gel, the latter modifying the C/S and A/S ratios as a function of either the silica or the lime-based concrete waste and the glass content of the mixtures. A higher degree of polymerization, morphology, and sodium content of C-H-S gel formed when glass was added.